Extended vs Bolus Infusion of Broad-Spectrum β-Lactams for Febrile Neutropenia: An Unblinded, Randomized Trial. (28th March 2018) - Ram, Ron; Halavy, Yael; Amit, Odelia; Paran, Yael; Katchman, Eugene; Yachini, Bruria; Kor, Svetlana; Avivi, Irit; Ben-Ami, Ronen
Abstract : Extended infusion of β-lactam antibiotics in patients with febrile neutropenia resulted in a higher rate of clinical success compared with standard bolus infusion. The benefit of extended β-lactam infusion was greatest among patients with pneumonia. Abstract: Background: Febrile neutropenia may be a sign of severe infection and is associated with significant morbidity and mortality in high-risk patients with hematologic malignancies. Extended infusion of β-lactam antibiotics is associated with greater clinical response than is bolus infusion in nonneutropenic critically ill patients, but data are lacking for febrile neutropenic patients. Methods: We designed a single-center, nonblinded, randomized trial to compare extended infusion (4 hours) and bolus infusion (30 minutes) of piperacillin-tazobactam or ceftazidime in high-risk patients with febrile neutropenia. The primary endpoint was overall response on day 4, defined as the combination of resolution of fever, sterile blood cultures, resolution of clinical signs and symptoms, and no need for a change in the antibiotic regimen. Outcome was adjudicated by investigators blinded to treatment allocation. Results: Of 123 enrolled patients, 105 had febrile neutropenia and were included in the intention-to-treat analysis: 47 in the extended infusion arm and 58 in the bolus infusion arm. Overall response occurred in 35 (74.4%) patients treated with extended infusion and 32 (55.1%) patients treated with bolus infusion ( P = .044). The superiority of extended infusion was greatest for patients with clinically documented infections (overall response, 68.4% [13/19] vs 35.7% [10/28]; P = .039) and specifically for those with pneumonia (80% [4/5] vs 0% [0/8]; P = .007). Conclusions: Extended infusion of β-lactams is associated with superior treatment outcomes compared with bolus infusion for high-risk patients with febrile neutropenia. The benefit of extended β-lactam infusion may be greatest for patients with pulmonary infections. Clinical Trials Registration: NCT02463747.